Kunst des Westens : Deutsche Kunst 1945-1960 : Kunstausstellung der Ruhrfestspiele Recklinghausen 1996. - Burrichter, Rita; Dienst, Rolf-Gunter; Golinski, Hans Günter; von Graevenitz, Antje; Peters, Andrea; Ruhrberg, Bettina & Karl; Schwalm, Hans-Jürgen; Schönenberg, Erik; Stachelhaus, Heiner; Ullrich, Ferdinand; Wedewer, Rolf; Kunsthalle Recklinghausen, Recklinghausen; et al. (Köln : Wienand Verlag, 1996)
Ackermann, Max ; Antes, Horst ; Baumeister, Willi ; Berke, Hubert ; Bissier, Julius ; Brüning, Peter ; Buchheister, Carl ; Camaro, Alexander ; Cavael, Rolf ; Cimiotti, Emil ; Dahmen, Karl Fred ; Deppe, Gustav ; Fleischmann, Adolf Richard ; Fruhtrunk, Günter ; Gaul, Winfred ; Geiger, Rupprecht ; Gilles, Werner ; Girke, Raimund ; Goller, Bruno ; Götz, K.O. (Karl Otto) ; Graubner, Gotthard ; Grieshaber, HAP ; Grochowiak, Thomas ; Hajek, Otto Herbert ; Hartung, Hans ; Heiliger, Bernhard ; Heldt, Werner ; Hermanns, Ernst ; Hoehme, Gerhard ; Kiess, Emil ; Klapheck, Konrad ; Kricke, Norbert ; Loth, Wilhelm ; Mack, Heinz ; Marcks, Gerhard ; Mataré, Ewald ; Matschinsky-Denninghoff, Brigitte & Martin ; Meistermann, Georg ; Nay, Ernst Wilhelm ; Pfahler, Georg Karl ; Piene, Otto ; Ritschl, Otto ; Schultze, Bernard ; Schumacher, Emil ; Seitz, Gustav ; Siepmann, Heinrich ; Sonderborg, K.R.H. ; Thieler, Fred ; Trier, Hann ; Uecker, Günther ; Uhlmann, Hans ; Vordemberge-Gildewart, Friedrich ; Werdehausen, Hans ; Werner, Theodor ; Winter, Fritz ; Wols
biografie
Kunst des Westens : Deutsche Kunst 1945-1960 : Kunstausstellung der Ruhrfestspiele Recklinghausen 1996, 5. Mai bis 14. Juli 1996
Duits
boek
Keywords: Duitsland